PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE 3 MATA PELAJARAN IPAS SISWA KELAS V MI - Husniyah, Nova Amirotul; Sri Enggar Kencana Dewi; Nor Kholidin (Universitas Islam Raden Rahmat Malang, 2025)
Abstrak Thel rapid advancementl of technologyl has significantlyl affected education, yet thel lack ofl students’ interest andl motivation still becomesl a challengel for teachersl in carryingl out effective learning. To overcome this, thel development ofl interactive learningl media using Articulatel Storyline 3l is considered necessary to enhance students’ interest, enjoyment, engagement, and acceptance. Thisl study aims tol develop interactivel learning medial based onl Articulate Storylinel 3 by employingl the Researchl and Developmentl (lR&D) methodl with thel ADDIE lmodel, whichl includes fivel stages: lAnalysis, lDesign, lDevelopment, lImplementation, andl Evaluation. Thel research results indicated that validation by materiall experts obtained anl average scorel of l92%, while medial experts achieved 85%. Both results were categorized as “very feasible.” Furthermore, smalll group trialsl produced anl average ofl 92.5%, largel group trialsl reached 93.5%, and teacher response questionnaires obtained 95%. The implementation stage was therefore categorizedl as “very practical.” Thesel outcomes confirm thatl the developedl product meets both feasibility and practicality standards. In conclusion, interactivel learning medial based onl Articulate Storylinel 3 isl highly feasible andl practical tol be appliedl in IPAS subject matter, especially in Chapter 8 Topic A, and canl serve asl an effectivel alternative tol improve learningl quality and increase student engagement. Keywords: Interactive Learning Media, Articulate Storyline 3, Science Abstrak Perkembangan teknologi yang telah mempengaruhi dunia pendidikan, serta kurangnyal minat danl motivasi siswal menjadi tantanganl bagi gurul dalam melaksanakanl pembelajaran. Oleh sebab itu, pengembanganl media pembelajaranl interaktif berbasisl Articulate Storylinel 3 diperlukan untukl meningkatkan ketertarikan, perasaan senang, keterlibatan siswa dan penerimaan. Penelitianl ini bertujuanl untuk mengembangkanl media pembelajaranl inetarktif berbasisl Articulate Storylinel 3. Metode yangl digunakan yaitu Researchl and Develophment (lR&D) denganl menggunakan modell ADDIE yangl terdiri daril lima tahapanl yaitu: lAnalysis, lDesign, lDevelopment, Implementationl dan lEvaluation. Hasill penelitian ini yaitu berdasarkan hasill validasi olehl ahli materil mendapatkan persentasel skor lrata-ratal 92% sedangkan ahlil media mendapatkan persentasel skor lrata-ratal 85%. Rekapitulasil angket padal tahap validasil memiliki kriterial “sangat layak”. Kesimpulannya produk medial pembelajaran interaktifl berbasis Articulatel Storyline 3 yangl telah dikembangkanl sangat layakl digunakan sebagail salah satu medial pembelajaran IPAS BAB 8 Topik A. 3) berdasarkan angket ujil coba kelompokl kecil mendapatkanl persentase skor 92,5% sedangkan ujil coba kelompokl besar mendapatkanl persentase skor rata-rata 93,5%, dan berdasarkan angket respon guru mendapatkanl persentase skorl rata-ratal 95%. Rekapitulasil angket padal tahap implementasi memiliki kriteria “sangat praktis”. Kesimpulannya produk media pembelajaran interaktif berbasis Articulate Storyline 3 yang telah dikembangkan sangat praktis untuk digunakan dalam pembelajaran. Kata kunci: Media Pembelajaran Interaktif, Articulate Storyline 3, IPAS